Coral Reef Coverage Percentage on Binor Paiton-Probolinggo Seashore - Dwi Budi Wiyanto (Journal of Marine and Aquatic Sciences, 2016)
The coral reef damage in Probolinggo region was expected to be caused by several factors. The first one comes from its society that exploits fishery by using cyanide toxin and bomb. The second one goes to the extraction of coral reef, which is used as decoration or construction materials. The other factor is likely caused by the existence of large industry on the seashore, such as Electric Steam Power Plant (PLTU) Paiton and others alike. Related to the development of coral reef ecosystem, availability of an accurate data is crucially needed to support the manner of future policy, so the research of coral reef coverage percentage needs to be conducted continuously. The aim of this research is to collect biological data of coral reef and to identify coral reef coverage percentage in the effort of constructing coral reef condition basic data on Binor, Paiton, and Probolinggo regency seashore. The method used in this research is Line Intercept Transect (LIT) method. LIT method is a method that used to decide benthic community on coral reef based on percentage growth, and to take note of benthic quantity along transect line. Percentage of living coral coverage in 3 meters depth on this Binor Paiton seashore that may be categorized in a good condition is 57,65%. While the rest are dead coral that is only 1,45%, other life form in 23,2%, and non-life form in 17,7%. A good condition of coral reef is caused by coral reef transplantation on the seashore, so this coral reef is dominated by Acropora Branching. On the other hand, Mortality Index (IM) of coral reef resulted in 24,5%. The result from observation and calculation of coral reef is dominated by Hard Coral in Acropora Branching (ACB) with coral reef coverage percentage of 39%, Coral Massive (CM) with coral reef coverage percentage of 2,85%, Coral Foliose (CF) with coral reef coverage percentage of 1,6%, and Coral Mushroom (CRM) with coral reef coverage percentage of 8,5%. Observation in 10 meters depth resulted in coral reef coverage percentage of 63,33%. 75% of living coral found on this 10 meters depth are dominated by Acropora branching coral, while the rest 25,21% are filled by Acropora tabulate coral and non-Acropora coral in the life form of branching, massive, sub-massive, foliose, and mushroom, where coral Mortality Index (IM) reached 28,5%. The high number of coral reef coverage percentage on Paiton is caused by successful coral transplantation and low activity of society in this location. The domination of large size Acropora branching coral were estimated comes from a few types, showing that coral resulted from transplantation has grown large and form a complex 3 dimension structure that is suitable for the life form of fish and living benthic.